Evaluation of Different Seeding Methods for Cell-Seeded Collagen Matrix-Supported Autologous Chondrocyte Transplantation - Viganò, Marco; Lugano, Gaia; Colombini, Alessandra; De Luca, Paola; Perucca Orfei, Carlotta; Ragni, Enrico; de Girolamo, Laura (Joints, 2018)
Purpose The aim of the present study was to evaluate different methods for the intraoperative seeding of chondrocytes on commercially available collagen I/III matrix, in the context of cell-seeded collagen matrix-supported autologous chondrocyte transplantation (ACT-CS).Methods Human chondrocytes were enzymatically isolated from cartilage portion of discarded femoral heads of patients who underwent total hip replacement. Chondrocytes were cultured until passage 3, and then used for the experiments. The cells (5.0 × 105) were suspended in two different volumes, 75 and 250 µL, and seeded on a matrix sample with a surface of 1 cm2 by means of a micropipette. Moreover, the direct immersion of the matrix in the cell suspension was evaluated as a possible protocol for chondrocyte seeding. Cell adhesion was allowed for 10, 30, or 60 minutes in all samples before evaluation.Results Data showed that the seeding time did not affect cell viability and distribution, but there was a great difference between the two volumes of injection. In fact, the use of 75 µL significantly reduced cell viability with respect to both 250 µL seeding volume and the immersion protocol. Indeed, cell distribution resulted homogeneous in the samples seeded with the larger volume and with the immersion protocol.Conclusion The use of 250 µL/cm2 volume or the immersion protocol for 10 minutes are valuable methods for chondrocyte seeding on collagen matrix in an intraoperative scenario.Clinical Relevance The protocol of chondrocyte seeding in ACT-CS is extremely variable among available literature reports. Chondrocytes adhesion to the matrix represents a crucial step in this methodology, and the present study provides in vitro indication for the choice of the seeding protocol in the context of ACT-CS.
Keywords: ACT-CS; matrix; chondrocytes; cartilage; intraoperative application